Mansonia bonneae (diptera: culicidae) sebagai vektor utama filariasis yang disebabkan oleh Brugia malayi nonperiodik di daerah penduduk asli Dayak di Kalimantan Timur - Fransiskus Asisi Sudjadi, Fransiskus Asisi Sudjadi (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1999)
Background: Nonperiodic form of B. ma/ayi was recently reported from East Kalimantan by Sudjadi as a new sub-species of filarial worm. The parasite was highly prevalent among Dayak people living from shifting cultivation of paddy rice in deep forest. Wild mosquitoes exist in the highly endemic area of Krayan, Long Ikis district, Pasir regency.Objective: To show current transmission of filariasis and its main vector species in the area of indigenous inhabitants of Dayak.Method: Wild mosquitoes were collected using human bait by standard method at night and day time in different places in the Krayan area. Wild mosquitoes landing and feeding on him were collected, than killed in local laboratory, identified and dissected to find filarial larvae.Results: Seven genera or 21 species (amount of 22.942) of mosquitoes were collected from Krayan for dissection, and they were markly predominated by Mansonia (21.960 or 95.5%) mosquitoes. Transmission of filariasis was detected currently occured in the area with the main vector of Ma. bonneae. This mosquito species was not only discovered harbouring infective larvae of the disease, but was also found as markly predominant species among Mansonia collected, particulary in locations within the environment of thick forest.Conclusion: Current transmission of filariasis with Ma. bonneae, as the main vector recorded in the highly endemic area of indigenous Dayak people in Krayan, supports the nonperiodic form of B. malayi in East Kalimantan to be zoonotic, sylvanic and phyletically they are more primitive than the other B. malayi type.Key words: filariasis - nonperiodic form of B. malayi - transmission - main vector - Ma. bonneae